Regional Inequality in Sulawesi Island: The Role of Economic Growth, Investment, and Government Expenditure - Novita Sari Sari; Farida Millias Tuty; Andi Herman Jaya; Ahmad Syatir (STIE Amkop Makassar, 2026)
This study aims to analyze regional inequality in Sulawesi Island and evaluate the roles of economic growth, investment, and government expenditure in influencing interregional disparities. Utilizing panel data from six provinces in Sulawesi over the 2012–2022 period, the analysis employs the Panel Least Squares method with a Random Effects Model (REM) approach. The estimation results indicate that economic growth has a positive but statistically insignificant effect on inequality (p-value = 0.1261), while investment shows a negative and likewise insignificant impact (p-value = 0.3415). In contrast, government expenditure exerts a positive and statistically significant effect on regional inequality (p-value = 0.0080). The R-squared value of 0.832961 suggests that the model explains approximately 83.30% of the variation in regional disparities. Furthermore, the F-statistic test confirms the overall significance of the model (Prob. F-statistic = 0.000000). These findings imply that among the three examined variables, only government expenditure significantly influences regional inequality in Sulawesi during the study period. The results underscore the importance of fiscal policy orientation and investment strategies that prioritize equity in regional development